2017
DOI: 10.1111/sjop.12354
|View full text |Cite
|
Sign up to set email alerts
|

Death anxiety and visual oculomotor processing of arousing stimuli in a free view setting

Abstract: The main goal of this study was to determine how death anxiety (DA) affects visual processing when confronted with arousing stimuli. A total of 26 males and females were primed with either DA or a neutral primer and were given a free view/free choice task where eye movement was measured using an eye tracker. The goal was to identify measurable/observable indicators of whether the subjects were under the influence of DA during the free view. We conducted an eye tracking study because this is an area where we be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 88 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…Smaller pupil diameter is in the literature related to extremism [ 66 ]. The research findings related to familiarity and eye behavior is documented by the present author [ 54 , 59 , 60 ]. Acting out is a constructed behavior, as it is important concerning the execution of behavior acts due to radicalization.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Smaller pupil diameter is in the literature related to extremism [ 66 ]. The research findings related to familiarity and eye behavior is documented by the present author [ 54 , 59 , 60 ]. Acting out is a constructed behavior, as it is important concerning the execution of behavior acts due to radicalization.…”
Section: Resultsmentioning
confidence: 79%
“…These behaviors were chosen because they are well-documented findings or findings relevant to safety or security. For example, research findings related to sexual change and EA are found in many published articles [ 17 , 18 , 54 , 59 , 60 ]. Smaller pupil diameter is in the literature related to extremism [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations